ANALISIS PENGARUH VARIASI KECEPATAN PUTARAN BLOWER TERHADAP KINERJA KOLEKTOR PANAS TENAGA SURYA PELAT TEMBAGA DENGAN SEKAT VERTIKAL - Raden Hengki Rahmanto; Firmansyah .; Raden Bagus Suryasa Majanasastra (Jurnal Ilmiah Teknik Mesin, 2019)
The availability of energy resources in the world increasingly diminish. More scientist is questing other renewable resources. The solar air heater is a tool that used energy by absorbing solar radiation then convert into heat energy. The study tried to have some variations to the speed of the air flow rate with spin 2500 rpm, 3000 rpm and 3500 rpm and give vertical partitions to it.The aim of giving vertical partitions is to know the influence to the heat transfer rate and the efficiency value of it. The result of this study is the speed variations of the blower take effect to the heat transfer rate. This is shown from the study data for 5 days, the average value of the heat of the system at 3500 rpm rotation is 341.6 Watts, 3000 rpm rotation value 305.7 Watt, and 2500 rpm rotation value 249.3 Watt. The average value of efficiency at 3500 rpm is 49.60%, 3000 rpm rotation is 43.22% and at 2500 rpm the value is 37.33%. The highest system heat is 535.79 Watt with the highest delta input and output temperature of 49.7 ℃. While the highest heat absorber is 1280.15 Watt with the highest light intensity, which is 140100 Lux. With a variety of rotation speeds blower and vertical partitions, this tool is capable of producing the highest efficiency of 67.95%, and the lowest is 24.85%.